2012
DOI: 10.1080/08897077.2011.640187
|View full text |Cite
|
Sign up to set email alerts
|

Skills-Based Residency Training in Alcohol Screening and Brief Intervention: Results from the Georgia-Texas “Improving Brief Intervention” Project

Abstract: Alcohol screening and brief intervention (SBI) is recommended for all primary care patients but is underutilized. This project trained 111 residents and faculty in 8 Family Medicine residencies to conduct SBI and implement SBI protocols in residency clinics, then assessed changes in self-reported importance and confidence in performing SBI and brief intervention (BI) rates. Clinicians reported significant increases in role security, confidence, and ability to help drinkers reduce drinking and decreased importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…14-17 A larger multisite trial showed increases only in screening rates. 18 Beginning in 2010, the Southeastern Consortium on Substance Abuse Training (SECSAT), one of the aforementioned recipients of SAMHSA residency training grants, used a novel approach to disseminate and implement SBI into clinical settings. This approach was informed by the grantees' prior experience with the Georgia-Texas "Improving Brief Intervention" project 18 and a recent review of SBI implementation strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14-17 A larger multisite trial showed increases only in screening rates. 18 Beginning in 2010, the Southeastern Consortium on Substance Abuse Training (SECSAT), one of the aforementioned recipients of SAMHSA residency training grants, used a novel approach to disseminate and implement SBI into clinical settings. This approach was informed by the grantees' prior experience with the Georgia-Texas "Improving Brief Intervention" project 18 and a recent review of SBI implementation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…18 Beginning in 2010, the Southeastern Consortium on Substance Abuse Training (SECSAT), one of the aforementioned recipients of SAMHSA residency training grants, used a novel approach to disseminate and implement SBI into clinical settings. This approach was informed by the grantees' prior experience with the Georgia-Texas "Improving Brief Intervention" project 18 and a recent review of SBI implementation strategies. 19 SECSAT sought to increase SBI rates in four primary care residency clinics by combining residency curriculum interventions with a comprehensive SBI implementation process.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Assessing the impact of SBIRT curricular interventions for trainees is challenging. Most published studies show improvement in attitudes, confidence and substance use related knowledge [8][9][10][11][12] and some have demonstrated improvement in SBIRT skills as measured by standardized patient assessments. 13,14 However, standardized patient exams may not reflect the "real world" application of clinical skills.…”
Section: Introductionmentioning
confidence: 99%
“…As explanation for this result, one can point out the lack of knowledge about this problem among health workers, a phenomenon well documented in the literature (7,11,(15)(16) which prevents the recognition of the problem and a more appropriate approach for these professionals in different health services (4,17) . This result also reflects the little attention being given to the issue of addictions in nursing syllabus (11)(12)18) which was also evidenced in this study where 60% of participants received no training on this topic during nursing education. Among those who reported receiving some content on the issue, most mentioned were offered between 5 and 10…”
Section: Discussionmentioning
confidence: 57%